The Effect of Motivation, Reward and Academic Supervision on Pedagogic Competence of Post-Certified Islamic Religious Education Teachers - Nur Widiastuti; Nyayu Khodijah; Abdurrahmansyah Abdurrahmansyah (STAI Hubbulwathan Duri, 2021)
The study aimed to analyze the effect of motivation, reward and academic supervision on the pedagogic competence of post-certified Islamic Religious Education teachers at Madrasah Tsanawiyah in East Lampung. The study used a quantitative approach with a survey method. The type of survey used was an explanatory analytic survey using cross-sectional. The population in the study were 176 certified Islamic Religious Education teachers from 90 schools, through simple random sampling to be 17 teachers from 9 schools. Tests and questionnaires did data collection. The data analysis technique was by analyzing data descriptions, testing assumptions/preconditions for linearity tests, and hypothesis tests, namely bivariate analysis and multivariate analysis. The study results indicated that the effect of motivation, reward, and academic supervision was 92.1% on pedagogic competence.